Root Canal Disinfection Potential of 5.25% Sodium Hypochlorite, 2% Chlorhexidine and 810nm Diode Laser-A Comparative In vitro Antimicrobial Study - Amit Arvind Agrawal; Swapnil Kolhe; Amit Sope; Dinesh Erlewad (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2016)
Background: The eradication of persisting bacteria, such as Enterococcus faecalis, is crucial for the long-term preservation of the endodontically treated tooth. Context and Purpose of the study: The aim of this research was to evaluate and compare the root canal disinfection potential of 5.25% sodium hypochlorite, 2% chlorhexidine gluconate and 810nm diode laser against control. Results: Adjunctive use of chemical disinfection by either 5.25% sodium hypochlorite or 2% chlorhexidine led to 100% microbial eradication as against diode laser which achieved 97.7% reduction as compared to baseline microbial count and 68.42% reduction after mechanical cleaning at the same dilutions. Main findings: Chemicals used in the study achieved greater disinfection than diode laser irradiation. Conclusions: 5.25% sodium hypochlorite or 2% chlorhexidine can be efficiently used as an adjuvant to mechanical root canal cleaning. Brief summary: A total of 20 extracted teeth, sectioned at cement-enamel junction, were divided into four groups of five teeth each. Control group: mechanical cleaning only; three test groups: mechanical cleaning followed by disinfection with 5.25% sodium hypochlorite or 2% chlorhexidine or 810nm diode laser. Pre and Post treatment microbial samples were collected and cultured. Potential Implications: A thorough mechanical instrumentation is crucial for success of any endodontic therapy and chemical or laser irradiation will only be helpful as an adjuvant.